Understanding migration aversion using elicited counterfactual choice probabilities - Gizem Koşar; Tyler Ransom; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2019)
Residential mobility rates in the United States have fallen considerably over the past three decades. The cause of the long-term decline remains largely unexplained. In this paper we investigate the relative importance of alternative drivers of residential mobility, including job opportunities, neighborhood and housing amenities, social networks, and housing and moving costs, using data from two waves of the New York Fed's Survey of Consumer Expectations. Our hypothetical choice methodology elicits choice probabilities from which we recover the distribution of preferences for location and mobility attributes without concerns about omitted variables and selection biases that hamper analyses based on observed mobility choices alone. We estimate substantial heterogeneity in the willingness to pay (WTP) for location and housing amenities across different demographic groups, with income considerations, proximity to friends and family, neighbors' shared norms and social values, and monetary and psychological costs of moving being key drivers of migration and residential location choices. The estimates point to potentially important amplifying roles played by family, friends, and shared norms and values in the decline of residential mobility rates.
Keywords: D84; J61; R23; 330; geographic labor mobility; migration; neighborhood characteristics